2009
DOI: 10.1677/jme-08-0112
|View full text |Cite
|
Sign up to set email alerts
|

Role of angiotensin II-induced rapid response genes in the regulation of enzymes needed for aldosterone synthesis

Abstract: Aldosterone is principally synthesized in the zona glomerulosa of the adrenal by a series of enzymatic reactions leading to the conversion of cholesterol to aldosterone. Angiotensin II (Ang II) is the major physiological regulator of aldosterone production acting acutely to stimulate aldosterone biosynthesis and chronically to increase the capacity of the adrenals to produce aldosterone. We previously defined eight transcription factors that are rapidly induced following Ang II treatment using three in vitro a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 72 publications
5
45
0
Order By: Relevance
“…7A and B for mRNA and protein, respectively). In agreement with the previously described role for the NGFIB family in CYP11B2 expression (19)(20)(21)(22), knockdown of NGFIB and NURR1 decreased AngIIstimulated induction of CYP11B2 (Fig. 7C, right).…”
Section: From H295r Cells After 3 H Of Incubation With Angii or Vehicsupporting
confidence: 92%
See 3 more Smart Citations
“…7A and B for mRNA and protein, respectively). In agreement with the previously described role for the NGFIB family in CYP11B2 expression (19)(20)(21)(22), knockdown of NGFIB and NURR1 decreased AngIIstimulated induction of CYP11B2 (Fig. 7C, right).…”
Section: From H295r Cells After 3 H Of Incubation With Angii or Vehicsupporting
confidence: 92%
“…After recovery for 24 h, cells were lysed, and luciferase activity was measured. previous study (20) (also see Discussion). Finally, we also confirmed that HSD3B2 was not responsive to AngII, irrespective of the presence of DN-NGFIB.…”
Section: From H295r Cells After 3 H Of Incubation With Angii or Vehicsupporting
confidence: 70%
See 2 more Smart Citations
“…31 Further, the binding of Ang II to AT1R enhances the activity of SRC and protein kinase C (PKC), which upregulates CYP11B2. 32, 33 Although many studies in animals, cells, and human populations have implicated SRC and CSK in blood pressure regulation, the mechanisms through which this occurs has not been determined. We have reported that knockdown and haploinsufficiency of Csk increase blood pressure through Src.…”
Section: Animal Research and Ethics Statementmentioning
confidence: 99%